The Effects of Servant Leadership, Supervision Competence, and Work Loyalty on Teacher Performance - Waldatun Thai' Atun; M. Syadeli Hanafi; Nandang Faturohman; Fajar Erlangga (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The primary emphasis of teacher performance lies in the strategies employed by educators to proactively enhance the academic achievements of their students. The aim of the research is to examine the relationship between servant leadership, supervisory competence, and teacher work loyalty on teacher performance. This research uses survey methodology, the research sample is 19 school principals and 81 public elementary school teachers in Ciwandan District, Banten Province, Indonesia. The sampling technique was carried out by random sampling. The data collection instrument for this investigation was a questionnaire. Data were analyzed using PLS path modeling. The results of the research show that servant leadership has a significant effect (p<0.05) on supervision competence, supervision competence has no significant effect (p>0.05) on teacher performance, servant leadership has a significant effect (p<0.05) on teacher performance , and work loyalty have a significant effect on teacher performance. Future research is expected to produce a servant leadership paradigm to encourage the growth of teacher performance for the benefit of the school. The implications of this research finding may provide a useful means for principals to self-reflect on their leadership, thereby improving the overall quality of their educational leadership institutions.